Unfavorable nutrient intakes in children up to school entry age: results from the nationwide German KiESEL study - Burgard, Leonie; Jansen, Sara; Spiegler, Clarissa; Brettschneider, Anna-Kristin; Straßburg, Andrea; Alexy, Ute; Storcksdieck genannt Bonsmann, Stefan; Ensenauer, Regina; Heuer, Thorsten (Frontiers in Nutrition, 2024)
Background: Nutrition in the first years of life is a cornerstone for child development and long-term health, yet there is a lack of current data on energy and nutrient intake among toddlers and preschoolers in Germany. Objective: To analyze energy and nutrient intake in toddlers (1-to 2-year-olds) and preschoolers (3-to 5-year-olds) in Germany and compare the results with the Dietary Reference Values (DRVs) by the European Food Safety Authority. Design: Dietary intake was assessed by weighed food record data (3+1 day) of 890 children from the representative cross-sectional Children's Nutrition Survey to Record Food Consumption (KiESEL), carried out in 2014-2017 as a module of the German Health Interview and Examination Survey for Children and Adolescents Wave 2. For the calculation of energy and nutrient intake, the German Nutrient Database BLS 3.02, LEBTAB, and a supplement database were used. Results: Median intakes of energy and most nutrients met or exceeded the DRVs in both toddlers and preschoolers. However, low intakes relative to DRVs were found for vitamin D (6-9 % of DRV, including supplements) and iodine (57-65 % of DRV). Age specific downward deviations were observed for iron intake in toddlers (75 % of DRV) and for calcium intake in preschoolers (67-77 % of DRV). In contrast, intakes were high for saturated fatty acids (SFA) (14-16 E%), mono-/disaccharides (60-87 g/day), and protein (2.1-2.6 g/(kg body weight*day)). Conclusions: Nutrient imbalances in toddlers and preschoolers in Germany, which are partly age-related, give rise to concern. Research is needed to determine if routine vitamin D supplementation should be extended beyond infancy. Public health efforts to increase the rate of use of iodized salt and to reduce the intake of SFA and mono-/disaccharides in children's diets are to be strengthened.